Effects of microwave frying on physicochemical properties of edible oils and quality of potato chips - Elfaitouri, Taher A.Houssein (2017)
Microwave frying is an alternative processing method for producing fried food products with the advantages of saving energy and time and improving both the nutritional quality and acceptability of fried foods by consumers. Thus, the effects of microwave frying on the properties of edible oils and the quality characteristics of fried foods should be studied using different techniques to obtain comprehensive data on the properties of microwave-fried products. In this study, the effects of microwave frying on the physicochemical properties of frying oils, namely, refined, bleached and deodorized (RBD) palm olein and corn oil, which have market acceptability and are widely used in cooking, were evaluated. Changes in physicochemical properties, including free fatty acids, acid value, peroxide value, panisidine value, TPM% TOTOX value, color, viscosity, rheological behaviors and thermal properties, were evaluated to monitor the quality and frying performance of frying oil. The experimental data highlighted that both studied frying oils exhibited oil stability against oxidation during the microwave frying process, RBD palm olein showed a comparatively lower degree as compared to corn oil. The studied oils exhibited Newtonian behavior, and there was a significant increase (P < 0.05) in the viscosity of both oils as the extent of frying increased. There was a significant (P < 0.05) difference in the color of the studied edible oils with increased extent of frying. The thermal properties of the oils were determined by differential scanning calorimetry (DSC). The melting point of RBD palm olein during the heating curve was in the range of -3.25 °C, and during the cooling curve it was in the range of 4.35 °C. A comparison of the average melting point values of corn oil revealed values of - 28.0 °C and 26.0 °C during the heating and cooling curves, respectively. The properties of microwaved potato chips, namely, moisture content, oil uptake, bulk density, particle density, porosity values, volumetric shrinkage, hardness, and color development, were also evaluated. The moisture content of potatoes decreased significantly (P < 0.05), whereas the oil content values of the potatoes increased significantly (P < 0.05), with increasing frying time and microwave power level. Moreover, the kinetics models gave a good and varied fit for moisture diffusion and oil transfer. Interestingly, the effective moisture diffusivity for potato chips fried in corn oil ranged between 6.36x10-9 and 12.68x10-9 m2/s and between 6.64x10-9 and 12.84x10-9 m2/s. The oil transfer rate constant ranged between 2.02x10-2 and 1.94x10-2 s-1 and between 1.89x10-2 and 1.95x10-2 for potato chips fried in RBD palm olein and in corn oil, respectively. The activation energy obtained from the Arrhenius plot for the effective moisture diffusivity ranged between 58.17 and 58.84 kJ/mol. Scanning electron microscopy images showed the structural changes at the surface of microwaved potato chips, revealing detailed and specific information to elucidate the relation between microwave frying processing conditions and fried food structure. In addition, confocal laser scanning microcopy (CLSM) images were obtained to observe the surface morphology and oil distribution of potato chips. The oil distribution in microwaved potato chips fried under different microwave frying conditions showed that a crust developed during microwave frying. Oil was trapped only in intercellular spaces, which was strongly linked to the microstructure (not only in intercellular spaces but also over some cells). The topographical data acquired by CLSM in reflective mode confirmed that several cells were broken during the cutting operation. CLSM image representation of the reconstructed surface of a microwaved potato chip allowed the oil location on the potato surface to be observed. The macrostructural properties of microwaved potato chips fried in RBD palm olein and corn oil were investigated, and the results showed volumetric shrinkage, thickness expansion and diameter change as a function of the moisture loss effect by the frying process conditions. Moreover, the hardness showed several fluctuations at 160, 170, and 180 °C. The texture of fried potato chips was soggy at 160 °C due to the short microwave frying process, which led to incompletely fried potato chips. The acrylamide content of potato chips was detected during the microwave frying process. The acrylamide levels in potato chips fried in corn oil ranged from 380 to 12,301 ppb. Meanwhile, the acrylamide levels in potato chips fried in RBD palm olein ranged from 282 to 13,230 ppb. Remarkably, 60% of the potato chips had high levels of acrylamide due to the high thermal process during microwave frying. It can be concluded that the microwave frying of potato chips caused the formation of lower amounts of oxidation products in RBD palm olein and corn oil, indicating a lower extent of oxidative degradation of the studied oils. In addition, the physical properties of the studied oils were investigated. Moreover, the quality characteristics of microwaved potato chips were obtained. The levels of acrylamide in microwaved potato chips were determined. In general, the microwave frying is an attractive process for food due to its applicability, convenience and low oxidative degradation.